Remembering Korea 1950 : a boy soldier's story - Shin, H. K. (Hyung Kyu), 1933- (University of Nevada Press, 2001)
"When the North Korean army invaded South Korea in June 1950, H.K. Shin was a sixteen-year-old high school student. The invasion of a country still reeling from decades of Japanese occupation and intense post-World War II political turmoil created a national disaster. Shin's school was closed, and he and his younger brother returned home. But the family was very soon forced to flee the invasion, and Shin ended up alone in Pusan, a refugee without resources or any means of support. To save himself from destitution, he lied about his age and volunteered for service in the South Korean army." "Shin's account of the months that followed is an intensely moving record of the Korean War from the perspective of an ordinary ROK Soldier. He recounts his hasty training and subsequent experiences as a battlefield soldier in North Korea, as a guard in a prisoner-of-war camp, and as a refugee once again retreating before the onslaught of the Chinese invasion. Through it all, Shin struggles to retain his humanity and pursue his education. In the process, the naive schoolboy becomes a man."--Jacket